Growing Threat Increased Carbapenem-Resistance among Klebsiella pneumoniae; Antibiotic Susceptibility Pattern of Klebsiella pneumoniae in a Tertiary Care Hospital - Selin, UGRAKLI; Metin, DOGAN (International Journal of Clinical Microbiology, 2020)
Background The morbidity and mortality associated with the multi drug resistant Gram negative bacterial infections pose a significant and growing challenge to clinical practitioners. Klebsiella pneumoniae, which is a substantial nosocomial pathogen and confer high levels of resistance to broad-spectrum antibiotics including carbapenems. The aim of this study is to determine the resistance profiles of Klebsiella pneumoniae strains isolated from various clinical specimens. Material and Method In this study, the antibiotic susceptibility profiles of 2452 Klebsiella pneumoniae strains isolated from various clinical specimens between July 2015 and November 2019 were considered retrospectively. Blood culture vials were incubated in Bac T / Alert 3D automated system, other samples were cultured on blood and Eosin Methylene-blue (EMB) medium. The identification and antibiotic susceptibility tests of the isolated bacteria were performed by VITEC 2 Compact ID-AST cards (BioMérieux, Marcy l’Etoile, Fransa) and the results were evaluated according to the standards of the Europian Committee on Antimicrobial Susceptibility testing (EUCAST). The first sample of each patient was included in the study. The strains with inappropriate results were re-studied with gradient agar diffusion test (BioMérieux, Marcy l’Etoile, Fransa). Results The study included a total of 2452 Klebsiella pneumoniae strains and the distribution of samples was as follows: 894 (36, 5 %) blood, 790 (32, 2%) bronchial lavage, 211 (8,6 %) wound, 148 (6 %) drainage, 148 (6 %) peritoneal fluid, 95 (3, 9 %) tracheal aspirates, 64 (2,6%) catheter, 62 (2,5 %) urine, 40 (1,6%) other samples (pleural fluid, cerebrospinal fluid, throat ). In this study, antibiotic susceptibility test results indicated that the resistance to tigecycline was lowest (0, 3%). High colistin resistance ratio (33, 5 %) in carbapenem-resistant Klebsiella pneumoniae was considered to be of concern. Conclusion In this study, high rates of resistance to carbapenems were noteworthy. Determination of hospital antimicrobial resistance rates will be useful in developing antibiotic use policies of each hospital, in the treatment of causative agents, in selecting antibiotics according to antimicrobial susceptibility.
Keywords: Klebsiella pneumoniae; antibiotic resistance; carbapenem; antibiotic stewardship; .